Optimization of combined active-passive electromagnetic shielding system for overhead power lines magnetic field normalization in residential building space - Kuznetsov, B. I.; Nikitina, T. B.; Bovdui, I. V.; Chunikhin, K. V.; Kolomiets, V. V.; Kobylianskyi, B. B. (Національний технічний університет "Харківський політехнічний інститут", 2025)
Normalization of overhead power lines magnetic field level in residential building. Goal. Normalization of overhead power line magnetic field by optimization of combined electromagnetic shielding system, consisting of active and passive parts, in residential building space based on magnetic field three-dimensional model. Methodology. Optimization of combined electromagnetic shielding system for initial magnetic field three-dimensional model solved based on multi-criteria two-player antagonistic game solution. Game payoff vector calculated based on finite element calculations system COMSOL Multiphysics package. Game solution calculated based on particles multiswarm optimization algorithms. Results. The results of theoretical and experimental studies of combined electromagnetic passive and active shielding system for magnetic field three-dimensional model in residential building from two-circuit overhead power transmission line with wires «Barrel» type arrangement presented. Scientific novelty. For the first time the method for normalization of overhead power lines magnetic field in residential building space based onoptimization of combined active-passive electromagnetic shielding system for magnetic field three-dimensional model developed. Practical value. Spatial location coordinates of shielding winding, currents and phases in shielding winding of robust active shielding system, geometric dimensions and thickness of electromagnetic passive shield calculated during optimization of combined electromagnetic shielding system for magnetic field three-dimensional model.

Нормалізація рівня магнітного поля повітряних ліній електропередачі в житлових будинках. Мета. Нормалізація рівня магнітного поля повітряних ліній електропередачі шляхом оптимізації комбінованої електромагнітної екрануючої системи, що складається з активної та пасивної частин, у просторі житлових приміщень на основі тривимірної моделі магнітного поля. Методологія. Оптимізація комбінованої електромагнітної екрануючої системи тривимірної моделі вихідного магнітного поля розраховується на основі рішення багатокритеріальної антагоністичної гри двох гравців. Вектор виграшів гри розраховується на основі кінцево-елементної системи обчислень COMSOL Multiphysics. Рішення гри розраховується на основі алгоритмів оптимізації мультироїв частинок. Результати. Наведено результати теоретичних та експериментальних досліджень комбінованої електромагнітної системи пасивного та активного екранування тривимірної моделі магнітного поля в житловому будинку від дволанцюгової повітряної лінії електропередач із розташуванням проводів типу «бочка». Наукова новизна. Вперше розроблено метод нормалізації магнітного поля повітряних ліній електропередачі в житловому приміщенні на основі оптимізації комбінованої активно-пасивної системи електромагнітного екранування тривимірної моделі магнітного поля. Практична значимість. Координати розташування екрануючих обмоток, струм і фаза в екрануючих обмотках робастної системи активного екранування, та геометричні розміри і товщина електромагнітного пасивного екрану розраховуються при оптимізації комбінованих електромагнітних екрануючих систем тривимірної моделі магнітного поля.
Keywords: overhead power line; magnetic field; combined electromagnetic active and passive shielding system; computer simulation; experimental research; повітряна лінія електропередачі; магнітне поле; комбінована електромагнітна активна та пасивна система екранування; комп'ютерне моделювання; експериментальні дослідження